Main Parameter Compensation Principles of Power Lines in Power System Networks - G. E. Pospelov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2009)
The paper contains systemization of principles and methods for parameter compensation of power lines in power system networks.